2013
DOI: 10.1021/jf401118n
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Acyloxonium Ions as Diagnostic Aids in the Characterization of Chloropropanol Esters under Electron Impact (EI), Electrospray Ionization (ESI), and Atmospheric Pressure Chemical Ionization (APCI) Conditions

Abstract: During mass spectrometric analysis of various lipids and lipid derivatives such as the chlorinated counterparts of triacylglycerols, the detailed structure of the characteristic and common ions formed under electron impact (EI), electrospray ionization (ESI), and atmospheric pressure chemical ionization (APCI) conditions by the loss of a single fatty acid remains ambiguous. These ions are designated in the literature as "diacylglyceride ions" and are frequently depicted with a molecular formula without showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Ions in series M can undergo pathway c to produce mainly the cyclic acyloxonium ion at m/z 135.53 through the displacement of the ester group at sn-1 position. The loss of the ester group at sn-1 positions 15 rather than at sn-2 supports a formation mechanism 12 involving the preferential displacement of the ester group from the less hindered position through an S N 2 mechanism. Furthermore, these studies have also demonstrated the following leaving group priority under electron ionization conditions; esters halides alcohols.…”
Section: Diagnostic Ions Of Chloropropanol Estersmentioning
confidence: 65%
See 4 more Smart Citations
“…Ions in series M can undergo pathway c to produce mainly the cyclic acyloxonium ion at m/z 135.53 through the displacement of the ester group at sn-1 position. The loss of the ester group at sn-1 positions 15 rather than at sn-2 supports a formation mechanism 12 involving the preferential displacement of the ester group from the less hindered position through an S N 2 mechanism. Furthermore, these studies have also demonstrated the following leaving group priority under electron ionization conditions; esters halides alcohols.…”
Section: Diagnostic Ions Of Chloropropanol Estersmentioning
confidence: 65%
“…The same ion series has also been observed under various soft ionization conditions 1,12 and has been referred to in the literature as diacylglyceride ions . This ion series could have great diagnostic utility during the analysis of CP esters 12 . Furthermore, isotope labeling studies 14 using CP acetates R CH 3 have confirmed the elemental composition of this ion.…”
Section: Formation Of Chlorinated Cyclic Acyloxonium Ions Pathway Cmentioning
confidence: 70%
See 3 more Smart Citations